SOSIO-ETNIESE DANSE VAN DIE VENDA VROU, by Cora Bumett-van Tonder, HAUM, Pretoria, 1987, 155pp, 62 line drawings, 23 colour plates, music and dance transcriptions, Tshivenda glossary, index, Afrikaans text. - Kruger, Jaco (International Library of African Music, 1996)
pages: 122-124
Keywords: African Music